Autonomous Triangulation and Dynamic Modelling of Uncooperative Space Objects using a Distributed Network of Remote Sensors - Jansen-Sturgeon, Trent (Curtin University, 2019)
This doctorate thesis describes improvements and novel approaches to triangulation, dynamic modelling, and orbit determination of observed meteoroids from fireball networks. Additionally, building on, and inspired by the distributed network approach utilised within the fireball community around the world, herein describes a new technique to space surveillance and tracking with the use of multiple, wide field-of-view, relatively low resolution, ground-based sensors.